2013
DOI: 10.1021/ja312115x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Molecular Clustering inside Nanopores on Desorption Processes

Abstract: Understanding the sorption kinetics of nanoporous systems is crucial for the development and design of novel porous materials for practical applications. Here, using a porous coordination polymer/quartz crystal microbalance (PCP/QCM) hybrid device, we investigate the desorption of various vapor molecules featuring different degrees of intermolecular (hydrogen bonding) or molecule-framework interactions. Our findings reveal that strong intermolecular interactions lead to the desorption process proceeding via an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 34 publications
3
24
0
Order By: Relevance
“…Previous studies also showed that QCM experiments performed with drop-cast films (deposited MOF mass 3-7 g) could be used to study the kinetics of the desorption processes of guest molecules from the pores of different MOFs. 31 LB films obtained at the best working conditions tested (MIL-101(Cr) + 1% BA) were then deposited onto QCM substrates at 12 mN·m -1 for CO 2 adsorption studies. The change in the resonant frequency after the deposition of the film was first used to determine the mass of MOF deposited using the Sauerbrey equation, 32 f = -C f ·m, where f is the observed frequency change in Hz, C f is the sensitivity factor of the QCM crystal (0.1834 Hz·ng -1 ·cm 2 ) provided by Inficon and m is the change in mass per unit area.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies also showed that QCM experiments performed with drop-cast films (deposited MOF mass 3-7 g) could be used to study the kinetics of the desorption processes of guest molecules from the pores of different MOFs. 31 LB films obtained at the best working conditions tested (MIL-101(Cr) + 1% BA) were then deposited onto QCM substrates at 12 mN·m -1 for CO 2 adsorption studies. The change in the resonant frequency after the deposition of the film was first used to determine the mass of MOF deposited using the Sauerbrey equation, 32 f = -C f ·m, where f is the observed frequency change in Hz, C f is the sensitivity factor of the QCM crystal (0.1834 Hz·ng -1 ·cm 2 ) provided by Inficon and m is the change in mass per unit area.…”
Section: Methodsmentioning
confidence: 99%
“…78 A further consequence of molecular clustering is that in concentration regions where 1/G i > 1, eqn (4) and (6) would yield the hierarchy of this unusual hierarchy is found for diffusion of methanol and ethanol in ZIF-8. 88 Tsotsalas et al 89 have investigated the kinetics of desorption of 1-butanol, diethyl ether, and n-pentane in CuBTC and found that molecular clustering effects, along with 1/G i > 1, provide an explanation for unusual desorption behaviours.…”
Section: Influence Of 1/c I On the Loading Dependence Of Diffusivitiesmentioning
confidence: 99%
“…These applications involve a process whereby the guest molecules diffuse in a spatial confinement on a length-scale below 1 nm and in a full flexible framework with breathing and gate-opening effects [1]. The diffusion rate influences the exchange phenomena between the host materials and the surroundings and influences the performance of MOFs' in their various applications [2][3][4]. Therefore, investigating guest diffusion within a MOF framework is an in demand research focus.…”
Section: Introductionmentioning
confidence: 99%